Electrical properties of a-C: Mo films produced by dual-cathode filtered cathodic arc plasma deposition - Sakon Sansongsiri (2018)
Molybdenum-containing amorphous carbon (a-C:Mo) thin films were prepared using a dual-cathode filtered cathodic arc plasma source with a molybdenum and a carbon (graphite) cathode. The Mo content in the films was controlled by varying the deposition pulse ratio of Mo and C. Film sheet resistance was measured in situ at process temperature, which was close to room temperature, as well as ex situ as a function of temperature (300-515 K) in ambient air. Film resistivity and electrical activation energy were derived for different Mo and C ratios and substrate bias. Film thickness was in the range 8-28 nm. Film resistivity varied from 3.55 × 10- 4 Ω m to 2.27 × 10- 6 Ω m when the Mo/C pulse ratio was increased from 0.05 to 0.4, with no substrate bias applied. With carbon-selective bias, the film resistivity was in the range of 4.59 × 10- 2and 4.05 Ω m at a Mo/C pulse ratio of 0.05. The electrical activation energy decreased from 3.80 × 10- 2to 3.36 × 10- 4 eV when the Mo/C pulse ratio was increased in the absence of bias, and from 0.19 to 0.14 eV for carbon-selective bias conditions. The resistivity of the film shifts systematically with the amounts of Mo and upon application of substrate bias voltage. The intensity ratio of the Raman D-peak and G-peak (ID/IG) correlated with the pre-exponential factor (σ0) which included charge carrier density and density of states. © 2008 Elsevier B.V.